The application of Swales’ model in writing a research article introduction - Burhanuddin Yasin; Hijjatul Qamariah (Universitas Syiah Kuala, 2014)
This research attempts to suggest an alternative solution for writers in general and graduate students in particular in writing a proper research article introduction. In order to do so, the authors explored how the Swales’ model is applied in writing a research article introduction. The exploration was approached through a library study on the Swales model application. Some previous studies applying Swales Model were gathered and categorized into three categories − application of Swales model on different types of genre besides the research article introduction, different discipline or field and the last is the application of Swales’ on the research article introduction across languages. Another three articles written by professional writers were also collected as samples of introductions that have successfully presented three obligatory moves – establishing a territory (Move 1), establishing a niche (Move 2) and occupying the niche or presenting the present work (Move 3) − proposed by Swales’ model. Those introductions were segmented into those three moves and analyzed based on a communication purpose in every step derived from each move. In order to add more comprehension about the model, an analysis was also conducted on introductions for seven articles in the English Education Journal (EEJ) published by the Graduate Program in English Language Education at Syiah Kuala University. The purpose of the analysis was to show the differences in structure of introductions organized without following the CARS Swales model. Conclusions are that the CARS Swales model is relevant for the teaching of introductions for research writing and it can be a guideline to teach students the moves and steps of this model for communication purposes.